Radio interference evaluations of photovoltaic modules for radio astronomy active antenna - Juswardy, Budi; Schlagenhaufer, Franz; Hall, Peter (2013)
This paper presents a study on potential radio frequency (RF) emissions from photovoltaic (PV) modules, designed to power a typical low-frequency Square Kilometre Array (SKA) antenna element. Both conducted and radiated emissions were investigated to assess the impact of RF emissions on receiver sensitivity. The objective is to develop a method to screen PV modules at the component level. The method is correlated with measured results when a module is powering an antenna element to ensure that any emissions will not degrade receiver performance, while meeting SKA site requirements.